Access to genetic resources between biodiversity protection and intra-generational solidarity (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In Italy, even before the recent Constitution amendment of article 9, biodiversity protection was at the centre of the national strategy adopted with the ratification law of the Convention on Biological Diversity (CBD). The CBD establishes the sovereign rights of nations to control access to their biological diversity to safeguard an equitable sharing of the benefits arising out of the utilization of genetic resources. The Nagoya Protocol, a supplementary agreement to the CBD implemented in Europe with two Regulations, sets out the general framework for access and benefit-sharing (ABS legal instruments). EU States have recently implemented these regulations and the author suggests endorsing a study on ABS in order to make the system for exchanging genetic resources more effective in the interests of the community. A sustainable use of biological diversity, preserved through the ABS mechanism, is fundamental to cope with climate change and achieve food security: this key objective requires solidarity between present and future generations.
Keywords: Biodiversity Protection; Access and Benefit Sharing; Nagoya Protocol; Genetic Resources; ABS Regulation